Development of a Village Information System for Acceleration of Village Services in Desa Tegal Kecamatan Kemang Bogor - Ardiansyah, Deden; Harsani, Prihastuti; Tosida, Eneng Tita; Saputra, Abimanyu Oki; Bhayangkari, Andhika (Universitas Trilogi, 2022)
The Village Information System (SID) is an information system that changes raw data into ready-to-use information. In addition, SID will provide convenience to village officials in providing services to the community. The development of this SID is expected to be able to provide acceleration and improve the performance of village officials in terms of service quality to the community, productivity, responsiveness, responsibility and productivity. The development of a village information system in service activities in Tegal village is a transformation from manual to computerized, so systematic efforts are needed in the preparation involving subjects, objects and methods related to the transformation process. The development of the village information system uses the software development life cycle (SDLC). Efforts to control the quality of the Tegal Village Information System use four characteristics of ISO 9126, to know that the parts in the application system have correctly displayed error messages if an error occurs in inputting data.The result of this service activity is that every Village Apparatus can understand the material that has been submitted and can practice the results of the village administration work in a computerized manner based on the Village Information System.